Aqueous leaf extract of Clinacanthus nutans inhibits growth and induces apoptosis via the intrinsic and extrinsic pathways in MDA-MB-231 human breast cancer cells - Marilyn Jane Yong; Ahmad Zaidi Tani; Falah Abass Mohamed Salih; Rahmawati Pare; Rina Norgainathai; Fong, Siat Yee (Wolters Kluwer - Medknow, 2021)
Background: Clinacanthus nutans possesses several reported biological activities against different human cancer cells. However, reports on the growth-inhibitory effect of C. nutans leaf extract on the aggressive triple-negative breast cancer cells and the mechanisms of induced-cell death in these cells are limited. Objectives: The study aimed to assess the anticancer efficacy and associated mechanisms of the crude aqueous extract of C. nutans leaves (cCN) in MDA-MB-231 triple-negative human breast cancer cells. Materials and Methods: The metabolic viability of the MDA-MB-231 cells following respective treatments with cCN was measured using an adenosine triphosphate luminescent assay. The mode of cell death in MDA-MB-231 cells induced by cCN was examined using a luminescence- and fluorescence-based assay and the mechanisms involved were evaluated by comparative analysis of gene expression by reverse transcription–quantitative polymerase chain reaction. Results: Dose- and time-dependent growth inhibition of MDA-MB-231 cells by cCN was observed (IC50: 191.20 μg/mL). cCN also induced apoptotic cell death in the treated cells via the intrinsic and extrinsic apoptosis pathways by affecting the mRNA expression levels of Bad, Bax, Bcl-2, Bcl-xL, and FasL. Conclusion: These results suggest that C. nutans can be used as a potential agent in the treatment and prevention of breast cancer.